Microeconomics - Besanko, David 1955- (John Wiley, 2011)
"Business professionals that struggle to understand key concepts in economics and how they are applied in the field rely on Microeconomics. The fourth edition makes the material accessible while helping them build their problem-solving skills. It includes numerous new practice problems and exercises that arm them with a deeper understanding. Learning by Doing exercises explore the theories while boosting overall math skills. Graphs are included throughout the mathematical discussions to reinforce the material. In addition, the balanced approach of rigorous economics gives business professionals a more practical resource."-- Provided by publisher.